Target Identification for Stereotactic Thalamotomy Using Diffusion Tractography - Kincses, Zsigmond Tamás; Szabó, Nikoletta; Valálik, István; Kopniczky, Zsolt; Dézsi, Lívia; Klivényi, Péter; Jenkinson, Mark; Király, András; Babos, Magor; Vörös, Erika; Barzó, Pál; Vécsei, László (PLOS ONE, 2012)
Background Stereotactic targets for thalamotomy are usually derived from population-based coordinates. Individual anatomy is used only to scale the coordinates based on the location of some internal guide points. While on conventional MR imaging the thalamic nuclei are indistinguishable, recently it has become possible to identify individual thalamic nuclei using different connectivity profiles, as defined by MR diffusion tractography. Methodology and Principal Findings Here we investigated the inter-individual variation of the location of target nuclei for thalamotomy: the putative ventralis oralis posterior (Vop) and the ventral intermedius (Vim) nucleus as defined by probabilistic tractography. We showed that the mean inter-individual distance of the peak Vop location is 7.33 mm and 7.42 mm for Vim. The mean overlap between individual Vop nuclei was 40.2% and it was 31.8% for Vim nuclei. As a proof of concept, we also present a patient who underwent Vop thalamotomy for untreatable tremor caused by traumatic brain injury and another patient who underwent Vim thalamotomy for essential tremor. The probabilistic tractography indicated that the successful tremor control was achieved with lesions in the Vop and Vim respectively. Conclusions Our data call attention to the need for a better appreciation of the individual anatomy when planning stereotactic functional neurosurgery.